2018
DOI: 10.1002/syn.22030
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular administration of growth hormone induces morphological changes in pyramidal neurons of the hippocampus and prefrontal cortex in adult rats

Abstract: A growing body of evidence suggests that growth hormone (GH) affects synaptic plasticity at both the molecular and electrophysiological levels. However, unclear is whether plasticity that is stimulated by GH is associated with changes in neuron structure. This study investigated the effect of intracerebroventricular (ICV) administration of GH on the morphology of pyramidal neurons of the CA1 region of the dorsal hippocampus and layer III of the prefrontal cortex. Male Wistar rats received daily ICV injections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Several reports suggest that GH levels reduce with aging (Ashpole, Sanders, Hodges, Yan, & Sonntag, ; Sattler, ). A recent report for our group demonstrated that GH induced an increase in dendritic length in layer 3 of the PFC and CA1 of the dorsal hippocampus (Olivarez‐Hernández et al, ). In addition, cognitive functions decline during aging and several reports have demonstrated an increase in the extracellular levels of glutamate, that in high levels may induce neurotoxicity (Brewer, ; Choi et al, ; Zoia et al, ) and also alter mitochondrial function (Avila et al, ; Choi et al, ; Plaitakis, Zaganas, & Spanaki, ), which results in reduced dendritic length (Jia et al, ).…”
Section: Discussionmentioning
confidence: 78%
“…Several reports suggest that GH levels reduce with aging (Ashpole, Sanders, Hodges, Yan, & Sonntag, ; Sattler, ). A recent report for our group demonstrated that GH induced an increase in dendritic length in layer 3 of the PFC and CA1 of the dorsal hippocampus (Olivarez‐Hernández et al, ). In addition, cognitive functions decline during aging and several reports have demonstrated an increase in the extracellular levels of glutamate, that in high levels may induce neurotoxicity (Brewer, ; Choi et al, ; Zoia et al, ) and also alter mitochondrial function (Avila et al, ; Choi et al, ; Plaitakis, Zaganas, & Spanaki, ), which results in reduced dendritic length (Jia et al, ).…”
Section: Discussionmentioning
confidence: 78%
“…This may indicate that treatment with the hormone has induced an increase in the number of neurons in this area, as we and others have shown in rats [ 10 , 11 ]. Another possibility is that GH has induced the outbreak of dendritic spines and changes in the length and density of pre-existing dendrites in the hippocampus, as has been shown to occur after intracerebroventricular administration of the hormone in adult rats [ 42 ]. If we could have used 3′-deoxy-3′-[18F] fluoro- l -thymidine instead of FDG, we could have detected whether the changes observed in PET-SCAN were due or not to adult neurogenesis, as a study has shown in adult rats [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second possibility is that GH induced sprout of dendritic spines and changes in the lenght and density of pre-existing dendrites in the hippocampus, as it has been demonstrated after intracerebroventricular administration of the hormone in adult rats [29]. However, this possibility does not exclude the one indicated above.…”
Section: Discussionmentioning
confidence: 93%